2007
DOI: 10.1097/00006199-200701000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Women With Breast Cancer and Their Partners

Abstract: Findings from this study support that these telephone-delivered psychosocial interventions were effective for decreasing symptoms of depression and anxiety to improve psychological quality of life when compared to an AC group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
167
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 28 publications
3
167
0
3
Order By: Relevance
“…The most significant aspect of QoL mentioned as psychological well-being in many studies (Vanderwerker et al, 2005;Wagner et al, 2006;Badger et al, 2007) although QoL has multidimensional aspects (Ogce et al, 2008;Yanez et al, 2011;Chopra and Kamal, 2012). Studies examining demographic variables and psychosocial characteristics of caregivers related to QoL found that being a woman, younger age, single, lower socioeconomic status, unemployment, low education (Mellon et al, 2006;Gorji et al, 2012) and also lack of personal and social support (Ogce et al, 2008) affect the QoL negatively.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant aspect of QoL mentioned as psychological well-being in many studies (Vanderwerker et al, 2005;Wagner et al, 2006;Badger et al, 2007) although QoL has multidimensional aspects (Ogce et al, 2008;Yanez et al, 2011;Chopra and Kamal, 2012). Studies examining demographic variables and psychosocial characteristics of caregivers related to QoL found that being a woman, younger age, single, lower socioeconomic status, unemployment, low education (Mellon et al, 2006;Gorji et al, 2012) and also lack of personal and social support (Ogce et al, 2008) affect the QoL negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
“…Interventions were grouped into two categories according to their main therapeutic approach: 'Cognitive Behavioural Skills Training' (CBST) (n=25), which focuses on illness cognitions, education, goal setting, and coping strategies such as problem solving and symptom management; and 'Relationship Counselling' (RC) (n=10), which addresses relationship difficulties such as sexual intimacy, partner supportiveness, and communication [38,51,45,52,53,54,55,56,57,58]. There was no noticeable effect of mode of delivery (faceto-face, telephone, online) on illness type or outcomes.…”
Section: Intervention Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Psychosocial interventions such as support from a nurse/breast care nurse, exercise, telephone counselling, computer/online support, psychological and psychiatric care and social supports have all been found to improve the psychosocial status of women diagnosed with breast cancer. [5][6][7] As a result, the clinical practice guidelines from the National Health and Medical Research Council of Australia for the psychosocial care of adults with cancer 3 highlight the need for further research regarding "strategies to improve the detection of psychological difficulties in people with cancer" (p. 136) and "optimal methods for psychosocial referral and practice strategies to improve uptake" (p. 136). Enhanced knowledge about the best way to detect and respond to patients' psychosocial needs is vital in empower-…”
mentioning
confidence: 99%